Does sports club participation contribute to physical activity among children and adolescents? A comparison across six European countries. Issue 8 (December 2019) - Kokko, Sami; Martin, Leena; Geidne, Susanna; Van Hoye, Aurelie; Lane, Aoife; Meganck, Jeroen; Scheerder, Jeroen; Seghers, Jan; Villberg, Jari; Kudlacek, Michal; Badura, Petr; Mononen, Kaisu; et al.
Aims: Insufficient physical activity (PA) is one of the largest public health challenges of our time and requires a multisectoral public-health response. PA recommendations state that all children and adolescents should accumulate at least 60 minutes of moderate-to-vigorous PA (MVPA) daily and carry out vigorous PA (VPA) three times weekly. While participation in sports club activities is known to enhance the probability of reaching the recommended overall PA level, less is known about the contribution of sports club participation to VPA, and few cross-national comparisons have been carried out. The purpose of this paper is to study whether participation in sports club activities is associated with meeting the overall PA and VPA recommendations among children and adolescents across six European countries, namely Belgium (Flanders), Czech Republic, Finland, France, Ireland and Sweden.Methods: Analyses were carried out on existing self-reported national data sets using descriptive statistics and logistic regression.Results: Results indicate that approximately two-thirds of children and adolescents take part in sports club activities in the given countries. Sports club participants were more likely to meet the overall PA recommendations (OR 2.4–6.4) and VPA recommendation (OR 2.8–5.0) than non-participants.Conclusions: The extent to which overall PA and/or VPA is gained through sports club participation versus other settings needs to be further studied. Nonetheless, it can be argued that sports clubs have an important position in PA promotion for younger populations.